Structure, Bonding, and Photoaffinity Labeling Applications of Dialkyldiazirines - Zhang, Tianyi; Ondrus, Alison E. (Synlett, 2021)
Dialkyldiazirine photoaffinity probes are unparalleled tools for the study of small molecule–protein interactions. Here we summarize the basic principles of structure, bonding, and photoreactivity of dialkyldiazirines, current methods for their synthesis, and their practical application in photoaffinity labeling experiments. We demonstrate the unique utility of dialkyldiazirine probes in the context of our recent photoaffinity crosslinking-mass spectrometry analysis to reveal a hidden cholesterol binding site in the Hedgehog morphogen proteins.1 Introduction2 Structure, Bonding, and Spectral Properties3 Photoreactivity4 Synthesis5 Application in Photoaffinity Labeling6 Discovery of a Cholesterol–Hedgehog Protein Interface7 Conclusions and Outlook
Keywords: diazirine; carbene; photoreactivity; chemical biology; protein-ligand interactions